2021
DOI: 10.3389/fcell.2021.642916
|View full text |Cite
|
Sign up to set email alerts
|

Hsa-miR-100-3p Controls the Proliferation, DNA Synthesis, and Apoptosis of Human Sertoli Cells by Binding to SGK3

Abstract: Human Sertoli cell is required for completing normal spermatogenesis, and significantly, it has important applications in reproduction and regenerative medicine because of its great plasticity. Nevertheless, the molecular mechanisms underlying the fate decisions of human Sertoli cells remain to be clarified. Here, we have demonstrated the expression, function, and mechanism of Homo sapiens-microRNA (hsa-miR)-100-3p in human Sertoli cells. We revealed that miR-100-3p was expressed at a higher level in human Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Gene therapy strategies related to male infertility patients have been conceived. Hsa-miR-100-3p provides a new epigenetic regulator for proliferation, DNA synthesis and apoptosis of human Sertoli cells by binding to SGK3, providing new clues for gene therapy of male infertility (Liu et al 2021 ). For the gene therapy for male infertility caused by problems related to testicular and sperm gene expression, related studies have reported that through testicle-mediated gene transfer (TMGT) and sperm-mediated gene transfer (SMGT) to transfer genes from somatic cells into testicle and sperm, with sperm deliberately used as a gene transfer vector (Coward et al 2007 ).…”
Section: Potential Therapeutic Measures For Diabetes-induced Male Inf...mentioning
confidence: 99%
“…Gene therapy strategies related to male infertility patients have been conceived. Hsa-miR-100-3p provides a new epigenetic regulator for proliferation, DNA synthesis and apoptosis of human Sertoli cells by binding to SGK3, providing new clues for gene therapy of male infertility (Liu et al 2021 ). For the gene therapy for male infertility caused by problems related to testicular and sperm gene expression, related studies have reported that through testicle-mediated gene transfer (TMGT) and sperm-mediated gene transfer (SMGT) to transfer genes from somatic cells into testicle and sperm, with sperm deliberately used as a gene transfer vector (Coward et al 2007 ).…”
Section: Potential Therapeutic Measures For Diabetes-induced Male Inf...mentioning
confidence: 99%